2019
DOI: 10.1002/jctb.6095
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous separation, concentration and determination of trace fluoroquinolone antibiotics in environmental samples using a polymer aqueous two‐phase system coupled with HPLC

Abstract: BACKGROUND Fluoroquinolone antibiotics and their metabolites can accumulate in soil and water. Trace amounts of fluoroquinolone antibiotic residues in the environment necessitate the pretreatment of samples prior to analysis. In this work, a polyoxyethylene cetyl ether (POELE20)–NaH2PO4 aqueous two‐phase system (ATPS) was combined with high‐performance liquid chromatography (HPLC) to separate and determine trace quantities of ciprofloxacin (CIP), norfloxacin (NRF) and pefloxacin (PEF) in environmental samples.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Sun et al [134] separated and identified trace amounts of ciprofloxacin (CIP), norfloxacin (NRF), and pefloxacin (PEF) in environmental samples using the polyoxyethylenecetyl ether/ NaH 2 PO 4 ATPS combination with HPLC. The recovery efficiency of CIP was 92.08-99.50 %, and that of NRF and PEF was 93.40-99.30 %, respectively.…”
Section: Environmental Remediationmentioning
confidence: 99%
“…Sun et al [134] separated and identified trace amounts of ciprofloxacin (CIP), norfloxacin (NRF), and pefloxacin (PEF) in environmental samples using the polyoxyethylenecetyl ether/ NaH 2 PO 4 ATPS combination with HPLC. The recovery efficiency of CIP was 92.08-99.50 %, and that of NRF and PEF was 93.40-99.30 %, respectively.…”
Section: Environmental Remediationmentioning
confidence: 99%
“…The further development and application of hydrogen energy need to be achieved by preparing efficient, stable, and inexpensive photocatalytic materials. [1][2][3][4] However, unsatisfactory visible light absorption capacity and easy recombination of photo-generated charge carriers are still the key factors to restrict the reinforcement of photocatalytic performance. 5,6 Numerous studies have shown that well-matched band alignments and effective construction methods of semiconductor materials can largely improve the photocatalytic hydrogen production activity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to establish a sensitive and efficient method for the detection of antibiotic residues in honey. 10 Among the reported literature studies, several analytical methods have been established for the detection of trace compounds in food, which include high performance liquid chromatography (HPLC), 1,2,[11][12][13][14] liquid chromatography tandem mass spectrometry (LC-MS/MS), 6,[15][16][17] microbial assays-HPLC, 8 b-CD/ATP composite-HPLC, 5 enzyme-linked immunosorbent assay (ELISA), 18 capillary electrophoresis (CE), 4,19 and micellar electrokinetic capillary chromatography (MECC). 7 Microbial assays require the cultivation or purchase of different microorganisms, and microorganisms have strict requirements on the living environment.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, high performance liquid chromatography (HPLC), which also has the advantages of rapidity, efficiency, automation and high sensitivity, is widely used for the analysis of honey. 14 However, honey, one of the most complex natural foods, contains approximately 200 substances, and higher levels of compounds such as reducing sugars, phenols and pigments can produce strong matrix disturbances. 5 Also, since the antibiotic residues in honey are at low levels, extraction and concentration are required prior to liquid phase analysis.…”
Section: Introductionmentioning
confidence: 99%